Nicotianabenthamiana, a Surrogate Host to Study Novel Virulence Mechanisms of Gram-Positive Bacteria, Clavibacter michiganensis, and C. capsici in Plants - Park, In Woong; Hwang, In Sun; Oh, Eom-Ji; Kwon, Choon-Tak; Oh, Chang-Sik (Frontiers in Plant Science, 2022)
Clavibacter michiganensis is a Gram-positive bacterium that causes bacterial canker and wilting in host plants like tomato. Two major virulence genes encoding a cellulase (celA) and a putative serine protease (pat-1) have been reported. Here we show that Nicotiana benthamiana, a commonly used model plant for studying molecular plant-pathogen interactions, is a surrogate host of C. michiganensis and C. capsici. When a low concentration of two Clavibacter species, C. michiganensis and C. capsici, were infiltrated into N. benthamiana leaves, they caused blister-like lesions closely associated with cell death and the generation of reactive oxygen species and proliferated significantly like a pathogenic bacterium. By contrast, they did not cause any disease symptoms in N. tabacum leaves. The celA and pat-1 mutants of C. michiganensis still caused blister-like lesions and cankers like the wild-type strain. When a high concentration of two Clavibacter species and two mutant strains were infiltrated into N. benthamiana leaves, all of them caused strong and rapid necrosis. However, only C. michiganensis strains, including the celA and pat-1 mutants, caused wilting symptoms when it was injected into stems. When two Clavibacter species and two mutants were infiltrated into N. tabacum leaves at the high concentration, they (except for the pat-1 mutant) caused a strong hypersensitive response. These results indicate that C. michiganensis causes blister-like lesions, canker, and wilting in N. benthamiana, and celA and pat-1 genes are not necessary for the development of these symptoms. Overall, N. benthamiana is a surrogate host of Clavibacter species, and their novel virulence factors are responsible for disease development in this plant.